Ali je uporaba kognitivnih modulatorjev smiselna pri zdravljenju bipolarne motnje razpoloženja? - Kržišnik, Julija (Medicinski razgledi, 2011)
A significant proportion of patients with bipolar disorder do not respond satisfactorily to conventional pharmacological treatment with lithium, anticonvulsants, antipsychotics and antidepressants. Several studies point to high risk for chronic illness and relapse despite receiving available therapy.At this moment we do not even have a common definition for treatment-resistant bipolar disorder, which makes assessing the number of patients refractory to treatment very difficult. Not only resistance to treatment, but also the evidences of cognitive decline in chronic patients speak for the need for complementary therapies. Cognitive modulators such as donepezil, galantamine, rivastigmine and memantine are drugs that are primarily used in treating various forms of dementia. This paper collects currently available data on the use of cognitive modulators as augmentation therapy of treatment-resistant bipolar disorder and in treatment of cognitive decline in this disease. Encouraging results of studies and case reports suggest that further research into the use of cognitive modulators in bipolar mood disorder is reasonable, primarily in terms of controlled randomized double-blind studies.
Keywords: Bipolar Disorder; Psihoze manično-depresivne; Drug Therapy; Memantin; Cognition Disorders; Spoznavne motnje; Memantine; Galantamin; Galanthamine; Zdravila, ostanki; psihoze; Drug Residues; bipolarna motnja razpoloženja; zdravljenje; therapy